2016
DOI: 10.1016/j.jppr.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

MHD flow of a nanofluid in an expanding or contracting porous pipe with chemical reaction and heat source/sink

Abstract: In the present investigation, an analytical analysis has been carried out to study the influence of chemical reaction on MHD flow of a nanofluid in an expanding or contracting porous pipe in the presence of heat source/sink. The pipe wall expands or contracts uniformly at a time dependent rate. Similarity transformations have been invoked to reduce the governing flow equations into coupled nonlinear ordinary differential equations. An analytical approach, namely the homotopy analysis method (HAM) is employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Srinivas et al [22] has been studied the flow of nanofluid within contracting/expanding porous pipe with chemical reaction and heat source/sink and found the analytical solution. Vijayalakshmi and Srinivas [23] has been studied the flow and heat transfer effects of a nanofluid inside expanding or contracting walls with thermal radiation.…”
Section: Using Double Perturbationmentioning
confidence: 99%
“…Srinivas et al [22] has been studied the flow of nanofluid within contracting/expanding porous pipe with chemical reaction and heat source/sink and found the analytical solution. Vijayalakshmi and Srinivas [23] has been studied the flow and heat transfer effects of a nanofluid inside expanding or contracting walls with thermal radiation.…”
Section: Using Double Perturbationmentioning
confidence: 99%
“…Waqas et al [ 10 ] described a magneto hydrodynamic (MHD) mixed convection flow of micropolar liquid caused by a nonlinear stretched sheet under convective conditions. Srinivas et al [ 11 ] investigated the effect of a chemical reaction on the MHD flow of a nanofluid in a porous pipe that was expanding or contracting in the presence of a heat source/sink. Habib et al [ 12 ] analyzed numerical simulations for slip impacts on MHD nanofluid in the presence of an electromagnetic field and gyrotactic microbes under the influences of activation energy and heat radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been devoted to studying this process using different solution methods and geometries. Fractional derivatives, which are quite helpful in evaluating numerical values of key parameters that affect the abovementioned problem has been considered by Jamil et al, 18,19 Tanveer et al, 20 and Ullah et al 21 Also, studies on different geometries such as the vertical plate, [22][23][24][25][26][27][28][29] the stretching surface, [30][31][32][33][34][35][36] and so on have been presented in the literature. Khan et al 37 used the stretching sheet to explore the impact of chemical reaction on the heat and mass transfer of an MHD Powell-Eyring fluid flow in the presence of thermal diffusion and Joule heating and revealed that momentum slows down while concentration thickens as chemical reaction rises.…”
Section: Introductionmentioning
confidence: 99%